DETERMINAN OBESITAS PADA WANITA PASCA MENOPAUSE DI KOTA BOGOR TAHUN 2014 - Riyadina, Woro; Kodim, Nasrin; Madanijah, Siti (PERSATUAN AHLI GIZI INDONESIA, 2017)
In Indonesia, the trends of the prevalence of obesity is incresing from year to year, especially in the group of postmenopausal women. Further analysis purposes determine the primary determinant of obesity in postmenopausal women in the city of Bogor A number of samples analyzed 888 postmenopausal women from subset data of research